Metadiscourse Markers: Frequency and Errors Made by EFL Students - Junaity Soften Sine; Rosdiana Mata (Journal of Foreign Language Teaching and Learning, 2022)
To present a skillfully written abstract, an author should apply some strategies. One of them is the application of Metadiscourse Markers, which provides readers with linguistic features that will help them quickly get the gist of the entire research. Studies have examined the metadiscourse markers in abstracts of theses and published article journals written by Indonesian, but only a few used a corpus-based approach and analyzed the errors simultaneously. This study, therefore, aimed at finding the frequency of Metadiscourse Markers and grammatical errors made by Accounting Department students of Kupang State Polytechnic in their final papers’ abstracts. A corpus-based approach was applied by using AntConc Version 3.5.9 concordance tool. The study showed that interactive markers occurred more frequently than interactional resources. Moreover, grammatical errors were related to applying punctuation (comma), plural forms, verb tenses, and modality. This study suggests the teaching material includes the features of Metadiscourse Markers in abstract writing and further emphasizes the grammar on topics where students performed errors.